The Youngest Case of Metachronous Bilateral Acinic Cell Carcinoma of the Parotid Gland: A Case Report and Literature Review - Raid Alhayaza; M. Anas Dababo; Suresh Velagapudi (Case Reports in Otolaryngology)
Introduction. Acinic cell carcinoma (ACC) is a low-grade malignant salivary neoplasm that represents 17% of all salivary gland malignancies. It has a tendency to affect young individuals, especially females. ACC mainly originates in the parotid gland and has a potential for recurrence and metastases. Rarely, ACC can affect both parotid glands in a single individual. A bilateral ACC of the parotid gland could either present as a synchronous or a metachronous tumor. Case Report. Our patient is a 19-year-old female known case of ACC of the right parotid gland. The tumor was resected in December 2017. After 3 years, she presented with a left parotid pain and swelling, which raised the suspicion of a contralateral metachronous tumor of the left parotid gland. In September 30, 2020 we proceeded with ultrasound-guided fine needle aspiration of the left intraparotid lesion, and the results turned out to be consistent with ACC. Here, we report a case of a 19-year-old female presenting with metachronous bilateral ACC of the parotid gland with an interval of 3 years, which is the 6th of its kind in the literature and the youngest amongst them. Conclusion. Despite the rareness of metachronous occurrence of bilateral ACC of the parotid gland, it is still encountered in the medical practice. Here, we are highlighting the importance of follow-up with a periodic clinical and radiological examinations, bearing in mind the contralateral nonaffected parotid gland.